An Assessment of the Implementation of Socioeconomic Rights in Nigeria - Olorunfemi, Ubose Osoname; Omoruyi, Eseosa Kolleta (NIU Journal of Legal Studies, 2026)
The socio-economic landscape of Nigeria is characterized by sharp contradictions, abundant natural resources, widespread poverty, and insufficient access to basic services. Despite constitutional guarantees, the country is struggling to ensure basic rights to education, healthcare, and a satisfactory environment. This study examines the implementation of socio-economic rights in Nigeria, highlighting the challenges that hinder their effective realization, and assessing the progress made to date. Key issues are critically assessed, including ineffective policy implementation, limited institutional capacity, and environmental degradation. In addition, the analysis examines the legal frameworks, political initiatives, and institutional mechanisms established to promote socio-economic rights. The research shows that, although some progress has been made, particularly in legislation and international cooperation, there are still significant gaps in translating policy into tangible results. This assessment highlights the need for a multifaceted approach to addressing the socio-economic issues facing Nigeria. Recommendations include strengthening the institutional framework, enhancing accountability, and supporting inclusive participation in policy development processes. Ultimately, this research aims to contribute to the ongoing discourse on promoting socio-economic justice and human dignity in Nigeria, highlighting the need for coordinated efforts among the government, civil society, and international partners. Keywords: Socioeconomic Rights, Nigeria, Policy Implementation, Human Development, Sustainable Governance